(untitled) (Perioperaciina Medicina, 2019)
Under conditions of wide increased resistance of pathogens of infectious complications to antimicrobial agents, a considerable attention is paid to the use of antiseptic drugs. The research of their antimicrobial efficacy remains valid for substantiation of the rational use. The purpose was to carry out a comparative study of the antimicrobial efficacy of medicinal antiseptic agents based on decamethoxine and povidone-iodine. In the study there was examined antimicrobial activity of mentioned antiseptics against 682 clinical strains of microorganisms (A. baumannii, S. aureus, P. aeruginosa, Enterococcus spp., E. coli, Enterobacter spp., K. pneumoniae, Proteus spp.), isolated from patients with infectious complications. Minimum inhibitory and bactericidal concentrations of 1–2– 10 % iodine, 0.02 % decamethoxine (decasan) were determined. Antimicrobial efficacy of medicines, based on studied antiseptics was evaluated with the use of an index of antiseptic activity, calculated by means of commonly used methods. The study revealed high bactericidal properties of decasan against clinical strains of S. aureus, Enterococcus spp., E. coli, K. pneumoniae and Enterobacter spp. The advantages of antimicrobial activity of decamethoxine-based antseptis (decasan, p < 0.001) were proved. Iodine has expressed antimicrobial properties against Enterococcus spp., S. aureus, A. baumannii, bacteria of the Enterobacteriаcеae family and P. aeruginosa. It is proven that the dissolution of povidone-iodine leads to the reduction of the antimicrobial efficacy of 2 % antiseptic solution. There was found inefficacy of 1 % povidone-iodine against infectious agents (p < 0.001). Thus, the leading Gram-positive (S. aureus, Enterococci) and Gram-negative pathogens (Escherichia, Klebsiella, Enterobacteria, Acinetobacteria, Pseudomonas) have a sensitivity to iodine and to domestic preparation based on decamethoxin 0.02 % (decasan), with a definite advantage of the antimicrobial properties of the latter to Gram-positive and some Gram-negative microorganisms (p < 0.001).